2014
DOI: 10.1371/journal.pone.0106585
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Cyanotoxins on the Hypothalamic–Pituitary–Gonadal Axis in Male Adult Mouse

Abstract: BackgroundMicrocystins LR (MC-LR) are hepatotoxic cyanotoxins that have been shown to induce reproductive toxicity, and Hypothalamic–Pituitary–Gonadal Axis (HPG) is responsible for the control of reproductive functions. However, few studies have been performed to evaluate the effects of MC-LR on HPG axis. This study aimed to investigate the MC-LR-induced toxicity in the reproductive system of mouse and focus on the HPG axis.MethodsAdult male C57BL/6 mice were exposed to various concentrations of MC-LR (0, 3.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…MC-LR exposure led to an initial increase and subsequent decrease in the expressions of Fsh␤, Lh␤, and the secretion of FSH, LH, and testosterone. Similarly, Xiong et al [67] also demonstrated that MC-LR impaired spermatogenesis possibly through the direct or indirect inhibition of GnRH synthesis at the hypothalamic level in C57BL/6 mice.…”
Section: Pure Microcystins (-Lr) (Table 2)mentioning
confidence: 81%
See 3 more Smart Citations
“…MC-LR exposure led to an initial increase and subsequent decrease in the expressions of Fsh␤, Lh␤, and the secretion of FSH, LH, and testosterone. Similarly, Xiong et al [67] also demonstrated that MC-LR impaired spermatogenesis possibly through the direct or indirect inhibition of GnRH synthesis at the hypothalamic level in C57BL/6 mice.…”
Section: Pure Microcystins (-Lr) (Table 2)mentioning
confidence: 81%
“…These results showed that oxidative stress was responsible for apoptosis induced by MC-LR, and the reduced production of testosterone in Leydig cells could result in reproductive toxicity [62]. However, two studies later by the same group [51,66] and a further study [67] reported that MC-LR did not enter and had no cytotoxicity on Leydig cells. Because MC-LR was not observed to be distributed to Leydig cells in vitro, the authors inferred that in the acute/subacute experiment, MC-LR did not directly act on the testosterone synthesis pathway in Leydig cells.…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations
“…Any abnormality in the system can lead to infertility. [88][89][90] If the brain is unable to produce gonadotropic releasing hormone (GnRH), this disorder results in a lack of testosterone and stopping sperm production. 91,92 Lack of GnRH causes a group of disorders known as hypogonadotropic hypogonadism.…”
Section: Hormonal Defectsmentioning
confidence: 99%